IMPACT OF THE CARDIOVASCULAR POLYPILL (TRINOMIA) ON CHRONIC KIDNEY DISEASE. PROSPECTIVE REAL-LIFE DATA. (June 2022) - Cuadrado-Payán, Elena; Rodríguez-Espinosa, Diana; Casals-Urquiza, Joaquim; Risco-Zevallos, Jimena Del; Hermida, Evelyn; López-Romero, Luis Carlos; Rodas, Lida; Broseta, Jose Jesús
Abstract : Objective: Cardiovascular diseases are the leading cause of mortality and morbidity worldwide. Moreover, chronic kidney disease (CKD) patients exhibit significantly higher incidence and prevalence of cardiovascular events. In this population, used to a high burden of pills, the importance of a polypill-based treatment strategy increases to simplify treatment and ensure adherence. The cardiovascular polypill composition includes a lipid-lowering drug, antihypertensive agent, and antiplatelet therapy and is marketed in Spain since 2015 with the name of Trinomia. This report aims to obtain real-life data to evaluate ifTrinomia improves the standard of care. Design and method: Prospective, single-center, observational study of a cohort of CKD patients under the standard of care starting any combination of Trinomia in secondary prevention. Patient demographics, clinical history, blood pressure, and analysis of blood lipids, albumin-to-creatinineratio, and estimated glomerular filtration rate were measured at baseline and 6 and 12 months after starting treatment Results: A total of 49 patients (35 males) were included, with a mean age of 78, 83 years (range 51–95). 91, 83% had hypertension, 63, 26% with type 2 diabetes and 2, 04% with type 1 diabetes. Regarding the cause of secondary prevention, 75, 4% had cardiovascular disease, 16, 4% had a stroke, and 8.16% had both. All laboratory results are displayed in table 1. Conclusions: Although most of the variables studied, probably because it was a small group of patients with adequate baseline control, did not reach statistical significance, some results are worth noting. eGFR is 3 points higher at one year, with a reduction in UACR, which does not reach statistical significance but translates into a lower hyperfiltration without worsening renal function or an increase in serum potassium. In addition, there was a 5-point decrease in systolic blood pressure and a 3-point in diastolic (n.s.), and a better lipid profile is achieved, with a 10-point reduction in LDL and a 24-point reduction in triglycerides.